IMPLEMENTATION OF CHANGE MANAGEMENT ON TEACHER PERFORMANCE IN ISLAMIC EDUCATIONAL INSTITUTIONS - Risnamajasari, Risnamajasari; Urbaningkrum, Santi Mahmuda; Perawironegoro, Djamaluddin; Rusdiana, Rusdiana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The decline in teacher performance has an impact on the quality of education in an organization or institution including Islamic educational institutions. Therefore, Islamic educational institutions as an organization require a systematic and dynamic change or improvement so that teacher performance becomes a form of sustainable development in the future. The purpose of this study is to determine the management of change in Islamic educational institutions, and its implementation on teacher performance. The method used in this study is qualitative research with a literature study approach. Data is processed with the steps of research, reading, screening, data management, and drawing conclusions. The results of this study indicate that there are 6 variables that influence an organization in making changes, namely organizational structure, values, culture, organizational systems, technology, and organizational strategy. In addition, there are two ways that can be done to implement changes in Islamic educational institutions so that the organization can develop optimally. The first method includes formulating an Islamic education system, designing quality education in Islamic educational institutions, and reconstructing values ​​in Islamic educational institutions. Then the second includes getting support and involvement from people who are key to formal and informal leaders, developing strong plans, supporting consistent plans and behaviors, developing activities and programs that support successful implementation and become a critical part of the overall plan, celebrating short-term and long-term successes, and communicating non-stop. In addition, it is also known that changes or improvements in teacher performance can be made based on Lewin's change model which consists of the unfreezing stage, the move met stage, and the refreezing stage.